Addenda et corrigenda la „Flexiunea verbală în limba româna" - Cychnerski, Tomasz (Wydawnictwo Naukowe Uniwersytetu im. Adama Mickiewicza w Poznaniu, 2005)
This paper introduces the necessary modifications and supplements to the work Verbal Inflection in Romanian, published in 1999 by the same author. The main modifications are: a new phonological inventory applied to the morphological analysis, a new functional definition of the subjunctive mood, the elimination of the infinitive from the inflectional system, a new type of inflectional root distinguished - extended root, a new set of affixes. They refer to all the inflectional phenomena and cause many minor changes of formal and functional nature.
Addenda et corrigenda to "The Verbal Inflection in Romanian"